Egypt: Impacts of the Ukraine and global crises on poverty and food security - Abay, Kibrom A.; Abdelradi, Fadi; Breisinger, Clemens; Xinshen Diao; Dorosh, Paul A.; Pauw, Karl; Randriamamonjy, Josee; Raouf, Mariam; Thurlow, James (International Food Policy Research Institute, 2022)
Global food, fuel, and fertilizer prices have witnessed rapid and significant increase in recent months, driven largely by the fallout from the ongoing war in Ukraine and associated sanctions im-posed on Russia. Other factors, including governments’ responses and export bans, have also con-tributed to rising prices (Laborde and Mamun 2022). Palm oil and wheat prices increased by 56 and 100 percent in real terms, respectively, between June 2021 and April 2022, with most of the in-crease occurring since February 2022.